2007
DOI: 10.1016/j.taap.2006.09.019
|View full text |Cite
|
Sign up to set email alerts
|

The influence of water mixtures on the dermal absorption of glycol ethers

Abstract: Glycol ethers are solvents widely used alone and as mixtures in industrial and household products. Some glycol ethers have been shown to have a range of toxic effects in humans following absorption and metabolism to their aldehyde and acid metabolites. This study assessed the influence of water mixtures on the dermal absorption of butoxyethanol and ethoxyethanol in vitro through human skin. Butoxyethanol penetrated human skin up to sixfold more rapidly from aqueous solution (50%, 450 mg/ml) than from the neat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 28 publications
4
16
0
Order By: Relevance
“…Finally, flux from neat BE is substantially smaller (Region III) than from the 50% solutions and similar to that from the 10% BE solution. Similar observations have also been reported for other glycol ethers (Dugard et al, 1984;Traynor et al, 2007a;Venier et al, 2004;Wilkinson and Williams, 2002). It is important to note that the flux numbers presented in Fig.…”
Section: Introductionsupporting
confidence: 87%
“…Finally, flux from neat BE is substantially smaller (Region III) than from the 50% solutions and similar to that from the 10% BE solution. Similar observations have also been reported for other glycol ethers (Dugard et al, 1984;Traynor et al, 2007a;Venier et al, 2004;Wilkinson and Williams, 2002). It is important to note that the flux numbers presented in Fig.…”
Section: Introductionsupporting
confidence: 87%
“…In both species, the absorption flux obtained with 50 % nVP was twofold higher than with neat nVP. This was expected as results published by Traynor et al (2007) for human skin exposed in vitro to neat or aqueous mixtures of 2-be revealed percutaneous absorption of 2-be to be fivefold higher for a 50 % solution compared to neat 2-be (2.26 and 0.39 mg/ cm 2 /h, respectively; 200 µl/cm 2 applied). When the solution was applied at 20 µl/cm 2 , there was still a fourfold difference (0.19 ± 0.03 and 0.04 ± 0.01 mg/cm 2 /h, respectively).…”
Section: Discussionsupporting
confidence: 71%
“…similarly, for many other amphiphilic compounds, skin permeation was enhanced for aqueous solutions compared to neat compounds. For example, the absorption fluxes for ethoxyethanol (Traynor et al 2007), diethylene glycol (mono) butyl ether acetate (Venier et al 2004) andisopropanol (korinth et al 2012) were found to be between threeand more than tenfold higher for diluted solutions compared to their neat counterparts. For Frasch et al (2014), this phenomenon of neat absorption rates being less than absorption rates for dilute solutions is caused by dehydratation of skin, which is related to the specific concentration dependence of the thermodynamic activity of water for the compound in water.…”
Section: Discussionmentioning
confidence: 99%
“…These results parallel the poor mammalian skin absorption characteristics of permethrin in a dry formulation (Minugel 200), and high absorption in emulsion formulation. Traynor et al (2007) showed that butoxyethanol penetrated excised human skin up to six fold more rapidly from aqueous solution (50%) than from the neat solvent. Likewise, ethoxyethanol penetration increased threefold in the presence of water (50%).…”
Section: Resultsmentioning
confidence: 99%